2014
DOI: 10.1371/journal.pone.0101209
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel GPVI Receptor Antagonists by Structure-Based Repurposing

Abstract: Inappropriate platelet aggregation creates a cardiovascular risk that is largely managed with thienopyridines and aspirin. Although effective, these drugs carry risks of increased bleeding and drug ‘resistance’, underpinning a drive for new antiplatelet agents. To discover such drugs, one strategy is to identify a suitable druggable target and then find small molecules that modulate it. A good and unexploited target is the platelet collagen receptor, GPVI, which promotes thrombus formation. To identify inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 50 publications
4
32
0
Order By: Relevance
“…In agreement with others [ 18 ] we have observed that losartan (22 μM) delayed collagen-triggered protein tyrosine phosphorylation and reduced its extent (data not shown). The phosphorylation of the GPVI signaling subunit FcRγ examined by immunoprecipitation, was reduced in the samples of losartan-treated platelets compared to control samples confirming that that losartan impacts the initial phase of the GPVI signaling pathway.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with others [ 18 ] we have observed that losartan (22 μM) delayed collagen-triggered protein tyrosine phosphorylation and reduced its extent (data not shown). The phosphorylation of the GPVI signaling subunit FcRγ examined by immunoprecipitation, was reduced in the samples of losartan-treated platelets compared to control samples confirming that that losartan impacts the initial phase of the GPVI signaling pathway.…”
Section: Resultssupporting
confidence: 93%
“…Losartan dose-dependently inhibited the aggregation of human washed platelets induced by 1 μg.mL -1 collagen with an IC50 of 6.5 μM ( Fig 1A ) in agreement with recently reported data [ 18 ]. Furthermore, losartan inhibited the exposure of P-selectin induced by 10 μg.mL -1 collagen with an IC50 of 6.3 μM.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Originally used in pain relief, aspirin is now additionally used alone or in combination with other antiplatelet treatments as a standard therapy for the primary and secondary prevention of heart attack and stroke. Losartan (an angiotensin II receptor 1 inhibitor) used in the treatment of hypertension was discovered using structure-based repurposing to have anti-GPVI effects (41). In a recent study investigating the effects of a therapeutic dose of losartan on collagen-induced platelet activation, however, no statistically significant differences were observed between treated and nontreated patients with respect to a biological antiplatelet effect (42).…”
Section: Repurposing Current Drugs As Gpvi-dependent Antiplatelet Agentsmentioning
confidence: 99%
“…Losartan, an angiotensin II receptor antagonist, has been proposed to inhibit clustering but not binding of GPVI to collagen [15,16], leading to inhibition of platelet activation in vitro and reduced platelet accumulation after carotid injury in mice [17][18][19][20]. Honokiol is a natural bioactive molecule isolated from Magnolia species, which is used in traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%